1991
DOI: 10.1002/j.1460-2075.1991.tb07994.x
|View full text |Cite
|
Sign up to set email alerts
|

The pim-1 oncogene encodes two related protein-serine/threonine kinases by alternative initiation at AUG and CUG.

Abstract: The pim‐1 gene is frequently found activated by proviral insertion in murine T cell lymphomas. Overexpression of pim‐1 in lymphoid cells by transgenesis formally proved its oncogenic potential. The pim‐1 cDNA sequence predicts that both murine and human pim‐1 encode a 34 kd protein with homology to protein kinases. In this study, we show that the murine pim‐1 gene encodes a 44 kd protein in addition to the predicted 34 kd protein. The 44 kd protein is an amino‐terminal extension of the 34 kd protein and is syn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
220
0

Year Published

1992
1992
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 289 publications
(235 citation statements)
references
References 52 publications
12
220
0
Order By: Relevance
“…The pim-1 gene was originally identi®ed as a common locus of retroviral insertion in Moloney murine leukemia virus (MuLV)-induced T cell lymphomas (Selten et al, 1986). The gene encodes a serine/ threonine kinase (Saris et al, 1991;Hoover et al, 1991) and is transcribed primarily in hematopoietic tissues. In addition expression is found in cells with high proliferative activity, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…The pim-1 gene was originally identi®ed as a common locus of retroviral insertion in Moloney murine leukemia virus (MuLV)-induced T cell lymphomas (Selten et al, 1986). The gene encodes a serine/ threonine kinase (Saris et al, 1991;Hoover et al, 1991) and is transcribed primarily in hematopoietic tissues. In addition expression is found in cells with high proliferative activity, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…First, c-Myc does not contain the substrate recognition sequence for Pim-1 kinase, (Arg/Lys) 3 -X-Ser/Thr-X' (X' is likely neither a basic nor a large hydrophobic residue) (Friedmann et al, 1992). Indeed, according to Saris et al (1991), c-Myc protein was not phosphorylated by Pim-1 in vitro. Second, the coexpression of Pim-1 did not enhance the transcriptional activation of a reporter plasmid by cMyc in transient chloramphenicol acetyl-transferase assays (TM, unpublished data).…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that Pim-1 is a protein-serine/ threonine kinase (Telerman et al, 1988;Hoover et al, 1991;Padma and Nagarajan, 1991;Saris et al, 1991). We therefore investigated whether the serine/threonine kinase activity of Pim-1 is required for the stimulation of c-Myc-mediated apoptosis.…”
Section: Pim-1 Stimulates Rather Than Inhibits C-myc-mediated Apoptosismentioning
confidence: 95%
See 2 more Smart Citations